The liver and muscle secreted HFE2-protein maintains central nervous system blood vessel integrity - Xue Fan Wang; Robin Vigouroux; Michal Syonov; Yuriy Baglaenko; Angeliki M. Nikolakopoulou; Dene Ringuette; Horea Rus; Peter V. DiStefano; Suzie Dufour; Alireza P. Shabanzadeh; Seunggi Lee; Bernhard K. Mueller; et al. (Nature Communications, 2024)
Abstract Liver failure causes breakdown of the Blood CNS Barrier (BCB) leading to damages of the Central-Nervous-System (CNS), however the mechanisms whereby the liver influences BCB-integrity remain elusive. One possibility is that the liver secretes an as-yet to be identified molecule(s) that circulate in the serum to directly promote BCB-integrity. To study BCB-integrity, we developed light-sheet imaging for three-dimensional analysis. We show that liver- or muscle-specific knockout of Hfe2/Rgmc induces BCB-breakdown, leading to accumulation of toxic-blood-derived fibrinogen in the brain, lower cortical neuron numbers, and behavioral deficits in mice. Soluble HFE2 competes with its homologue RGMa for binding to Neogenin, thereby blocking RGMa-induced downregulation of PDGF-B and Claudin-5 in endothelial cells, triggering BCB-disruption. HFE2 administration in female mice with experimental autoimmune encephalomyelitis, a model for multiple sclerosis, prevented paralysis and immune cell infiltration by inhibiting RGMa-mediated BCB alteration. This study has implications for the pathogenesis and potential treatment of diseases associated with BCB-dysfunction.